Using acoustic cameras to study vocal mobbing reveals the importance of learning in juvenile Arabian babblers - Guggenberger, Marie; Boonman, Arjan; Keynan, Oded; Yovel, Yossi (Frontiers in Bird Science, 2024)
When studying bird intra-and inter-specific interactions it is crucial to accurately track which individual emits which vocalization. However, locating sounds of free moving birds (and other animals) in nature can be challenging, especially in situations when many individuals call in spatial and temporal vicinity. In this paper, we will introduce the use of a hand-held acoustic camera which allows solving this problem. The system comprises of 64 microphones each sampling a wide angle at a rate of 200kHz. The system can localize up to dozens of nearby callers and it displays them on a visual image. We applied the system to localize and record vocalizations of Arabian babblers (Argya squamiceps) during snake-mobbing behavior.As the recorded babblers are ringed and therefore identifiable, we could use the calling order to analyse the vocalizing mob and to reconstruct a vocal social network depicting which individuals call after which individuals. Vocal networks in wild animals have so-far received limited research attention due to technological constraints. Acoustic analysis revealed that Arabian babblers call in a periodic pattern and with age specific pause lengths between different individuals. Mobbing events with young babblers display a lower vocal network density compared to only adult groups. Our approach demonstrates how this novel technology can be applied to reveal new insight about vocal events in group living wild animals. The approach can be elaborated to study intra-and inter-specific animal vocalizations.